Correlating Local Morphology and Charge Dynamics via Kelvin Probe Force Microscopy to Explain Photoelectrode Performance - Maryam Pourmahdavi; Mauricio Schieda; Ragle Raudsepp; Steffen Fengler; Jiri Kollmann; Yvonne Pieper; Thomas Dittrich; Thomas Klassen; Francesca M. Toma (PRX Energy)
Photoelectrochemical (PEC) cells have emerged as a promising and sustainable route for the production of valuable chemicals and have attracted significant attention over the last few decades. However, photoelectrodes, essential components of PEC devices, are limited by solar-to-hydrogen conversion efficiencies significantly below the theoretical values, as well as by low stability under working conditions. An important hurdle toward achieving high efficiency is the limited number of available tools that can directly probe the interplay between the local morphology and charge carrier transport dynamics within the photoelectrode top layer. This layer has different functions: providing photocatalytic active sites and protecting underlying layers. Therefore, the development of a powerful technique to reveal the influence of morphology on transport dynamics is crucial. In this work, we show how to precisely correlate local morphology with optoelectronic properties via the investigation of photoinduced charge transport processes, by time-dependent Kelvin probe force microscopy (KPFM) measurements. Our approach allows the extraction of time-dependent photovoltage for each pixel of a KPFM scan. We used crystalline-amorphous mixed phase TiO_{2} as a well-established model system to apply and validate our method. Through local correlations between structure-morphology and optoelectronic properties, our results reveal more efficient photoinduced charge separation on the regions corresponding to the crystalline TiO_{2} phase, which exhibit faster transport, and generate a significantly higher surface photovoltage signal (approximately 440 mV) upon UV illumination (super-band-gap illumination). This finding supports the considerable role of microstructure in charge carrier dynamics, and the ability of our analytical method to resolve it. The analysis technique outlined here should find broad applicability, enabling in-depth insight into the effect of local microstructure, and contributing to the design and development of more efficient photoelectrodes by tailoring of the microstructure at the nanoscale.